Multi-Features Skipping Rope / Mohamad Izrul Hafiz Hamzah - Hamzah, Mohamad Izrul Hafiz (2020)
The product that being sell by this company is multi-feature skipping rope. There are three additional function in this product which are heartbeat monitor, jumping counter and body temperature monitor. The target market of this product is people that involve in sport activities especially teenagers and adults. There is no product of skipping rope in the market that provide three functions altogether in market nowadays. This is the first product that come with three important functions for human. The price of this product is RM85. The profit of this products is 30% of the product price which is RM35. There are six top managements team in this company and we also have partners with another company that will manufacture our product. The company that will manufacture our product is DF Robotic Company.